A facile ion imprinted synthesis of selective biosorbent for Cu2+ via microfluidic technology. Issue 8 (6th March 2017) - Zhu, Yong; Bai, Zhishan; Luo, Wenqiang; Wang, Bingjie; Zhai, Linlin
Abstract: BACKGROUND: Heavy metal pollution has become one of the most serious environmental problems. Novel approaches are needed for removal of heavy metal from water. Copper, a familiar heavy metal, has attracted much attention for its remarkable toxic domino offect at elevated concentrations. RESULTS: A novel ion imprinted approach combined with microfluidic technology was explored. Cu 2+ was taken as ionic template and chitosan was used as carrier material. Chemical crosslinking was applied in the formation of imprinted sign. A selective biosorbent of ion‐imprinted microspheres (IIMS) with uniform size, regular shape and high performance for Cu 2+ had been prepared. The SEM, FTIR, EDS, XPS were employed to detect their distinct features. IIMS showed much higher adsorption capacity ( q m =81.97 mg g −1 ) than those non‐imprinted chitosan microspheres (CSMS). The adsorption isotherm fitted the Langmuir equation while thermodynamic adsorption results were considered strong proof of an adsorption exothermal process. IIMS exhibited excellent selectivity for Cu 2+ when competitive metal ions and Cu 2+ co‐existed together, which profited from the specific spaces of Cu 2+ template left after crosslinking and desorption. Results confirmed that chemical adsorption was dominant and amino played an important role in adsorption process. CONCLUSION: IIMS showed high adsorption capacity and excellent selectivity for Cu 2+ . Combining microfluidic technology with an ion‐imprinted method proved to be a promising process for preparing selective materials. © 2017 Society of Chemical Industry